1994
DOI: 10.1007/bf02691011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic ethanol consumption on gestation and lactation in rats

Abstract: Chronic consumption of ethanol during pregnancy and lactation may lead to abnormalities in the fetus or infant. A group of female Wistar rats was submitted to ethanol treatment over a period of a month. A pair-fed control group received sucrose solution isocaloric to ethanol and the control group received water "ad libitum." Afterward, the females were mated with males over a period of 20 days. At birth, each litter was maximized to eight pups and the remaining ones were decapitated to remove the fetal blood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Efficient utilization of energy due to probiotic yeasts, and presence of alcohol in the palm sap/wine products may have led to the reduction of the pups' weights. This observation agrees with the reports of Sreeranjitkumar et al, 32 Breese et al, 33 and Maldaner et al, 34 that administration of toddy/ethanol decreased the birth weight of pups.…”
Section: Discussionsupporting
confidence: 93%
“…Efficient utilization of energy due to probiotic yeasts, and presence of alcohol in the palm sap/wine products may have led to the reduction of the pups' weights. This observation agrees with the reports of Sreeranjitkumar et al, 32 Breese et al, 33 and Maldaner et al, 34 that administration of toddy/ethanol decreased the birth weight of pups.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggested that chronic consumption prolonged the duration of pregnancy, while acute consumption resulted in increased risk for earlyonset delivery. 22,23 These findings indicate two important factors caused either delayed or premature delivery: the pattern of consumption and timing of exposure. 10,14 In previous studies, it was shown that the administration of ethanol led to the inhibition of oxytocin release from the neurohypophysis.…”
Section: Discussionmentioning
confidence: 87%
“…The clinical application for the use of ethanol infusions in threatened premature labor was readily apparent, and ethanol has been used since the 1980s, with varying degrees of success, in attempts to treat and prevent preterm birth (Zervoudakis et a]., 1980). Although some data suggest that alcohol use during pregnancy may be associated with lengthened gestation and a decreased risk for preterm delivery (Fuchs et al, 1967;Hahn et al, 1984;Leichter and Lee, 1979;Maldaner et at., 1994;Meis et al, 1998;Wright et al, 1998), other studies suggest that alcohol consumption during pregnancy shortens gestation and increases the risk for premature delivery (Berkowitz et al, 1982;Hingson et al, 1982;Olegard et al, 1979;Ouellette et al, 1977).…”
Section: Discussionmentioning
confidence: 97%